Assessing the Quality of Wastewater for Farming Purpose in and around Various Industrial Areas of Jaipur City, Rajasthan - Singh, Vijendra; Singh Chandel, C.P. (Asian Journal of Chemistry, 2010)
The physicochemical properties of domestic and industrial effluents disposed of into ‘Amanishah Nala’ of Jaipur city, where this water is used for irrigation purpose. The results obtained in the present investigations revealed that the water quality for farming purpose was found to be suitable; however, specific contaminations with special reference to EC, Cl–, TH, TDS, COD and BOD in wastewater have been observed, which calls for at least primary treatment of wastewater before being used for irrigation.